Management of Learning Based on Pancasila Values in Early Childhood - Amstrong Harefa; Jesslyn Elisandra Harefa; Maria Magdalena Zagoto; Oskah Dakhi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The internalization of Pancasila is carried out from an early age. This is related to the problems in the community of the fading of the noble values of the Indonesian state's guidelines for life. The final goal of this study was to find the methods used by Teachers in instilling Pancasila values in early childhood in kindergarten. Qualitative research methods are used to achieve this goal by making kindergarten teachers as informants determined through purposive techniques and Snowball sampling. Data was collected by placing researchers as the primary "tool" supported by interviewing, observation, and documentation techniques. The netted data was analyzed with miles and Huberman's qualitative data analysis techniques. The results concluded that kindergarten teachers' level of knowledge and understanding about the types of learning methods in early childhood is quite good. Methods of planting Pancasila values used in some kindergartens in West Gunungsitoli Subdistrict include playing, telling stories, singing, conversing, demonstrations, role-playing, habituation methods, and tourism.